Building The Potential of Hearing-Impaired Youth Through The Art of Performing - Wiwatanant , Warattaya; Angasinha, Asst. Prof. Dr. Chatwarun (Journal of Dhamma for Life, 2025)
This article aims 1. To study the potential development of hearing-impaired youth through the art of performing puppet theater. 2. To study the cognitive progress of hearing-impaired youth through the art of performing puppet theater. It is a phenomenological qualitative research. Use in-depth interviews and focus groups. From key informants including a group of trainers, a group of normal youth A group of hearing-impaired youth, a group of school teachers who teach the disabled, a sign language teacher, and the president of the Rotary Association, totaling 46 persons. Scope of study area Setthasathien School under the Royal Patronage. Using the concept of Simpson's learning theory for developing practical skills (Simpson. 1972) There are 7 steps: 1. Perception 2. Readiness 3. Guided Response 4. Mechanism 5. Complex Overt Response 6. Adaptation 7. Origination. Results of the study according to objective 1 To study the potential of hearing impaired youth through the art of puppet theater. It was found that the teaching model for small puppet theater performances Under the curriculum "Study, Dance, Play" of the "Mae Nai Sippatham Group" Able to strengthen the potential of hearing-impaired youth through the art of performing puppet theater. The development is divided into 4 areas as follows: Area 1 physical development, area 2 emotional development, area 3 social development and area 4 intellectual development. Results of the study according to objective 2 To study the cognitive progress of hearing-impaired youth through the art of puppet theater performances. It was found that teaching and learning focused on using sight as a base. Helps enhance the cognitive progress of hearing-impaired youth through the art of performing puppet theater.